Cyclization of a Cellular Dipentaenone by Streptomyces coelicolor Cytochrome P450 154A1 without Oxidation/Reduction - Steven Kelly (Journal of the American Chemical Society, 2010)
We report a comprehensive genetic, metabolomic, and biochemical study on the catalytic properties of Streptomyces coelicolor cytochrome P450 (P450) 154A1, known to have a unique heme orientation in its crystal structure. Deletion of the P450 154A1 gene compromised the long-term stability of the bacterial spores. A novel dipentaenone (1) with a high degree of conjugation was identified as an endogenous substrate of P450 154A1 using a metabolomics approach. The biotransformation of 1 by P450 154A1 was shown to be an unexpected intramolecular cyclization to a Paterno-Buchi-like product, without oxidation/reduction